Exploring the Correlation between Peer Attachment and Emotional Regulation in Indonesian Special Needs Education - Ari, Made Loka Santi; Soetjiningsih, Christiana Hari (Jurnal Bimbingan dan Konseling Terapan, 2024)
This study explores the relationship between peer attachment and emotional regulation in high school students at the Special State School in Salatiga, Indonesia, focusing on those with special needs. Utilizing a quantitative approach with a correlational design, the research involved 33 students selected through purposive sampling. The Inventory of Parent and Peer Attachment (IPPA) and the Emotion Regulation Questionnaire (ERQ) were employed as measurement tools. Descriptive statistical analysis indicated that the majority of students exhibited high levels of peer attachment and moderate levels of emotional regulation. A positive correlation (r = 0.625, p<0.01) was found between peer attachment and emotional regulation, suggesting that higher peer attachment is associated with better emotional regulation skills. The study highlights the crucial role of peer relationships in the emotional and social development of students with special needs. Interviews with students revealed a preference for peer communication over family interaction, especially among those with hearing impairments and intellectual disabilities. However, challenges such as the reluctance to interact with people outside their community were noted, particularly among students with hearing impairments. The findings emphasize the need for educational strategies that foster positive peer interactions to enhance emotional well-being. Despite its focus on a single educational setting, the research offers valuable insights into the impact of peer relationships on emotional regulation, underscoring the importance of nurturing these interactions in special education contexts.